Feedback is the best way to see - Bunganic, B; Laclav, M; Zaruba, P; Belina, F; Ryska, M; Zavoral, M (Endoscopic ultrasound, 2014)
A 60-year-old man with past history of acute mild pancreatitis (AP) in 1997 and 2005, recently with repeated attacks of AP 5 times in last 2 years. Repeated endoscopic ultrasonography (EUS) showed 20 mm cyst in pancreatic body with 5 mm nodule, main pancreatic duct (MPD) 4-6 mm, fine-needle aspiration malignant cell negative, mucin positive. Computed tomography and magnetic resonance imaging of branch duct intraductal papillary mucosal neoplasms with 10 mm branch duct. From 2011 to 2013, the cyst was without progression in size or character. Due to clinical course of repeated AP, endoscopic retrograde cholangiopancreatography was recommended. It revealed dilated MPD 5-7 mm and 15 mm × 13 mm cyst in pancreatic body. Distal pancreatectomy was indicated because of clinical course and "worrisome EUS features" - MPD size and intramural nodule. In terms of having feedback, endosonographer use to examine every resected specimen of pancreas in our hospital just after surgery. The resected body with "sand glass" appearance of the cyst of size 3 cm was totally different from what we saw previously. We rewinded the previous EUS documentation and made a new evaluation. EUS is unique method for pancreatic tumors, but only in combination with real image of specimen makes endosonographer to bow up.